Burdened by History: Where does Museveni Go from here? - Ssali, Vick Lukwago (Aichi Gakuin University, 2016)
President Yoweri Kaguta Museveni of Uganda was ‘re-elected’ last month for a fifth term in office. Some may argue it is his sixth or even seventh term, if we include the honeymoon period between 1986, when the National Resistance Movement/Army took power, and 1996, when Ugandans went to the polls for only the second time since the 1962 pre-independence elections.
Keywords: history; Museveni